Manufacturing civil society principles, practices and effects - Brandsen, Taco.; Trommel, Willem; Verschuere, Bram.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Faced with falling social cohesion governments have sought to revitalise society by trying to reconstruct local communities, civil society and citizenship. As a result, civil society is increasingly brought within the realm of public management, subject to accountability and embedded in hierarchies the impact and origins of which this book explores.
Keywords: Science; Science; Science, general